Implementation of Patient Legal Protection in Internal Policy Implementing BPJS Health in Wangaya Hospital, Denpasar City - I Gusti Agung Dhian Maharani Swari Dewi; Ni Made Jaya Senastri; Ni Komang Arini Styawati (Jurnal Hukum Prasada, 2022)
Policies in the implementation of health services at BPJS Health there are still obstacles experienced by patients and the hospital. Legal protection in health services aims to ensure legal certainty obtained by patients, so that patients avoid losses when receiving health services that should be optimally provided by health workers. The purpose of this study is to examine the implementation of the internal policies established by the Wangaya Hospital, Denpasar City in the implementation of BPJS Health services and to examine the legal protection for patients in BPJS Health services at Wangaya Hospital Denpasar City. This study uses empirical legal research methods, using the approach to legislation, analysis of legal concepts and facts. The research location is at Wangaya Hospital, Denpasar City. The results of this study showed that the implementation of internal policies at Wangaya Hospital, Denpasar City in providing BPJS Health services, namely with the authority of hospitals to be able to formulate and implement hospital regulations (hospital by laws) which contain general hospital services policies that support corporate governance and good governance, clinical governance. In the implementation of BPJS Health at Wangaya Hospital, Denpasar City, there are obstacles, such as: obstacles in claiming, technical, procurement of medicines that are not available or not yet available at distributors. Meanwhile, legal protection in BPJS Health services where patients are BPJS Health participants to be able to fulfill their rights as participants or patients. Patient rights have been regulated in the Medical Practice Law, Health Law, and Hospital Law. Legal protection is provided by the BPJS Health and the Hospital, namely by establishing a PIC (Personal in Change) which functions to accommodate handling patient complaints or related to BPJS Health services.